(untitled) (Journal of Parents and Teachers, 2024)
The following article is a reflection on the misuse of the Physical Education subject in the present, analyzing the obstacles that contribute to this, as well as the impact it has on students. Additionally, it lists a series of requirements to address the situation and clarifies the role that teachers should play in these sessions.